Evaluation of psychiatric symptoms of children with Celiac Disease and their relationship with gluten-free diet and maternal factors - Hasret Ayyıldız Civan; Semra Yılmaz (Zaslavsky O.Yu., 2021)
Background. The purpose was to evaluate the quality of life scores and the adherence of gluten-free diet (GFD) in children with celiac disease (CD). The other objective was to determine the relevance of the maternal emotional status between the psychological adjustments and GFD compliance of the patients with CD. Material and methods. Children's depression inventory (CDI), Screen for Child Anxiety and Related Disorders (SCARED), Strength and Difficulties Questionnaire (SDQ), KINDer Lebensqualitätsfragebogen Questionnaire, Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) were administered to both children with CD healthy controls. Furthmore, the results were compared between the CD patients ant the healthy ones. Results. A total of 47 patients with CD, 33 healthy children and their mothers were enrolled. GFD-compliance rate, which was confirmed by antibody tests, was found to be 41.7 %. The scores of CDI, SCARED, and SDQ were significantly higher in CD patients than the healthy children. Moreover, the total scores of KINDL was significantly lower in CD group. Higher scores of BDI and BAI were found in the CD patients' mothers than the healthy group. In patients group there were positive-moderate statistically significant correlation detected between score of BDI, BAI of mothers and CDI, SCARED, SDQ scores of children. There were also negative statistically significant correlation between scores of BDI, BAI of mothers and KINDL scores of children. Conclusions. Increased prevalence of psychopathology and reduced quality of life have been clearly demonstrated in children with CD. Worse maternal psychosocial adjustment significantly associated with depressive symptoms in pediatric CD patients.